Improving Student Ability in Accounting Research Data Processing Using SPSS - Junjunan, Mochammad Ilyas; Jannah, Binti Shofiatul; Aristantia, Selvia Eka; Nawangsari, Ajeng Tita; Lating, Ade Irma Suryani; Aripratiwi, Ratna Anggraini; Nufaisa, Nufaisa (Universitas Ahmad Dahlan, 2024)
Background: Timely graduation is a critical goal for universities, but delays frequently arise from students' difficulties in processing quantitative data. Lecturers play a vital role in addressing this issue by offering targeted statistical support to help students improve their data analysis skills and complete their studies on time. Contribution: This activity equips final semester accounting students with skills to analyze and interpret research data using SPSS, guided by lecturers in utilizing technology for economic and business data processing. It also enables students to conduct advanced predictive analysis and classification for deeper insights.Method: This activity was carried out for 20 accounting final semester students at UIN Sunan Ampel Surabaya in four days. There are several stages done in this activity, including socialization and mapping, module creation, pre-test, implementation, and evaluation, and post-test on the analysis and interpretation of accounting research data. Results: The pre-test, evaluation, and post-test activities show that this activity significantly improved students' ability to analyze and interpret accounting research data using SPSS. The research themes covered included financial accounting, management accounting, sharia accounting, auditing, taxation, and public sector accounting. The satisfaction level reached 65%.